2023
DOI: 10.1002/advs.202306528
|View full text |Cite
|
Sign up to set email alerts
|

Hydro‐Sensitive, In Situ Ultrafast Physical Self‐Gelatinizing, and Red Blood Cells Strengthened Hemostatic Adhesive Powder with Antibiosis and Immunoregulation for Wound Repair

Lingling Shang,
Yonggan Yan,
Zhao Li
et al.

Abstract: Immediate and effective hemostatic treatments for complex bleeding wounds are an urgent clinical demand. Hemostatic materials with characteristics of adhesion, sealing, anti‐infection, and concrescence promotion have drawn growing concerns. However, pure natural multifunctional hemostatic materials with in situ ultrafast self‐gelation are rarely reported. In this study, a hydro‐sensitive collagen/tannic acid (ColTA) natural hemostatic powder is developed that can in situ self‐gel to form adhesive by the non‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In the meantime, as compared to the PA/PHMG(1) and PA/PHMG(2) surfaces, an obvious peak at 287.15 eV was observed, which is attributed to the much higher intensity of CN peak detected on the corresponding PA/PHMG(3) surface (Figure h), in accordance with the fact that PHMG possesses massive N species (amino and guanidino groups) and reflecting the successful deposition of PA/PHMG coating on PP meshes. In addition, the π–π* peak at 291.24 eV further confirmed the presence of PA in the PA/PHMG(3) surface …”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In the meantime, as compared to the PA/PHMG(1) and PA/PHMG(2) surfaces, an obvious peak at 287.15 eV was observed, which is attributed to the much higher intensity of CN peak detected on the corresponding PA/PHMG(3) surface (Figure h), in accordance with the fact that PHMG possesses massive N species (amino and guanidino groups) and reflecting the successful deposition of PA/PHMG coating on PP meshes. In addition, the π–π* peak at 291.24 eV further confirmed the presence of PA in the PA/PHMG(3) surface …”
Section: Resultsmentioning
confidence: 59%
“…In addition, the π−π* peak at 291.24 eV further confirmed the presence of PA in the PA/PHMG(3) surface. 33 Moreover, the WCA of pristine PP, PA/PHMG(1), PA/ PHMG(2), and PA/PHMG(3) was tested to investigate the hydrophilic properties of the different sample surfaces (Figure 2i). The pristine PP was inherently hydrophobic and showed a WCA of around 97.17°.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial performances of the ColTA-Zn adhesive were investigated to previous reports . Typically, ColTA-Zn powders (20, 50, and 80 mg) were added to 1 mL of normal saline to prepared material leach liquors.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, our previous study has demonstrated the biocompatibility of ColTA powder. 13 In this study, a live/dead cell staining assay was used for assessing the cytocompatibility. The results showed that after 48 h of culture with the ColTA-Zn material leach liquor, the proportion of living cells (green) of the ColTA-Zn group was similar to that of the control group (Figure 5a).…”
Section: Cytocompatibility and Antibacterial Performancementioning
confidence: 99%
See 1 more Smart Citation